2015
DOI: 10.1634/theoncologist.2015-0177
|View full text |Cite|
|
Sign up to set email alerts
|

Balancing Safety and Efficacy of Epidermal Growth Factor Receptor Inhibitors in Patients With Squamous Cell Carcinoma of the Head and Neck

Abstract: The epidermal growth factor receptor (EGFR) is overexpressed in more than 80% of squamous cell cancers of the head and neck (SCCHN). An evolving understanding of the role of EGFR in tumorigenesis has made the receptor an important therapeutic target in SCCHN. Several EGFR inhibitors (EGFRIs) are active in SCCHN, and their use is associated with improvement in progression-free survival and overall survival in various treatment settings. Nevertheless, EGFR inhibition is associated with significant mucocutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…EGFR and human papillomavirus (HPV) are biomarkers that have been most extensively studied in HNSCCs. While EGFR overexpression has correlated with disease progression in HNSCC [ 5 , 6 , 25 ], EGFR expression status did not predicts clinical outcomes in the RTOG 0522 trial of concurrent accelerated RT plus cisplatin with or without cetuximab [ 9 ]. Prospective studies have reported that patients with HPV-positive metastatic HNSCC tended to benefit from the addition of anti-EGFR agents to chemotherapy [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGFR and human papillomavirus (HPV) are biomarkers that have been most extensively studied in HNSCCs. While EGFR overexpression has correlated with disease progression in HNSCC [ 5 , 6 , 25 ], EGFR expression status did not predicts clinical outcomes in the RTOG 0522 trial of concurrent accelerated RT plus cisplatin with or without cetuximab [ 9 ]. Prospective studies have reported that patients with HPV-positive metastatic HNSCC tended to benefit from the addition of anti-EGFR agents to chemotherapy [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The epidermal growth factor receptor (EGFR) is expressed in about 80% of patients with HNSCC [ 5 ]. EGFR overexpression has been found to be an independent factor associated with unfavorable prognosis in these patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the EGFR inhibitor, gefitinib (Iressa), can enhance the apoptotic effects of cisplatin in SCC [17]. Clinical trials involving the combination regimens of anti-EGFR agents with immune checkpoint inhibitors are currently in progress for SCC of the head and neck [19,20]. In this study, we explored the role of Syk in EGFR signalling in three SCC cell lines (A431, CAL27, and SAS), analysed Syk expression in oral SCC cancer tissues, and determined the relationship between Syk activity and disease prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The epidermal growth factor receptor (EGFR) is a 170-kDa receptor tyrosine kinase expressed in epidermal tissues [4]. The high expression of EGFR -about ninety percent ** makes this target pivotal in HNSCC.…”
Section: Introductionmentioning
confidence: 99%